Interactive Theatre: An Alternative Method of Teaching and Learning for Rural Young Children in Sekolah Kebangsaan Pekan Ranau, Sabah - Marlenny Deenerwan (Wacana Seni Journal of Arts Discourse, 2024)
Compared with children in urban areas, children living in rural areas experience a severe lack of exposure to alternative teaching and learning activities to enhance their self-potential. This development affects their opportunity to explore knowledge comprehensively. The Education Development Master Plan by the Ministry of Education identified five education gaps in the Malaysian education system. Among them are the urban and rural gaps and the gap between student achievement levels. In Malaysia, most districts that recorded the lowest performance in Ujian Penilaian Sekolah Rendah are in Sabah and Sarawak. This fact is the foundation factor to justify the implementation of this study in Sekolah Kebangsaan Pekan Ranau, located in the rural district of Ranau in Sabah. A total of 60 level one students were involved in the research, which took place from 2017 until 2019. In other developments, the inclusion of theatre as part of the school curriculum in most urban areas in Malaysia has indicated a formal acceptance of the value of theatre as an educational tool. Therefore, this research focuses on using interactive theatre to develop teaching and learning strategies for young children in rural areas. Interactive theatre is a performance that engages the audience and makes them active participants in the show. It brings the audience into the same playing space as the actors and breaks the walls separating them from the actors’ world. Through practice-led research, the researcher conducted a workshop session that led to a live interactive theatre production. While the significant reference of this study is Dorothy Heathcote’s Mantle of the Expert, Piaget and Dewey’s concept of active learning was utilised to observe and analyse the research findings. This research indicates that interactive theatre activities successfully turn passive children into active participants. By getting the children involved in this performance, they shared the stage setting, became characters in the performance, and had the opportunity to change the direction of the play. As they immersed themselves in the performance, they unconsciously explored their ability to improvise the situation and articulate their opinion critically and creatively.